PENGARUH DISIPLIN KERJA, KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PDAM KABUPATEN SRAGEN - Rohwiyati, Rohwiyati; Sulistya, Sulistya; Azizah, Intan Nur (Universitas Of Surakarta, 2023)
This study aims to determine the effect of work discipline, compensation and work environment on the performance of PDAM Employees, Sragen Regency in 2022. This research was conducted to determine the effect both partially and simultaneously. This research is a quantitative case study. Primary data was obtained from research by distributing questionnaires to research respondents. The research population was 275 respondents, with sampling using the Simple Random Sampling technique, so the number of samples in this study was 73 respondents. Data analysis technique used is multiple linear regression test, f test, t test, and test the coefficient of determination. The results of this study indicate that partially the work discipline and compensation variables have a positive and significant effect on employee performance, while the work environment variable has a negative and significant effect on employee performance. Work discipline, compensation, and work environment variables simultaneously have a significant effect on employee performance. The influence of work discipline, compensation, and work environment variables is 58.5%.